2022
DOI: 10.1177/09504222221099198
|View full text |Cite
|
Sign up to set email alerts
|

Students’ work placement learning and employability nexus: Reflections from experiential learning and social cognitive career theories

Abstract: To curtail difficulties in higher education relating to students’ learning with few or no real-life examples, poor acquisition of practical skills, a lack of confidence concerning their prospective career, and a fear of unemployment, it is imperative to engage students in real-life work environments before graduation. Drawing on the integration of Experiential Learning Theory and Social Cognitive Career Theory, the authors explore the work placement learning (WPL), career decision self-efficacy (CDSE), engagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 65 publications
(109 reference statements)
4
16
0
Order By: Relevance
“…Previous studies (Chukwuedo and Ementa, 2022; Okolie et al, 2021a; Okorie et al, 2022; Otache and Edokpolor, 2022) have found a positive and significant link between WPL and perceived employability, and employability preparatory behaviours. These findings are relevant given that, through WPL, higher education institutions (HEIs) can partner with industry to offer students opportunities to gain a practical understanding of work-related theoretical knowledge they may have gained in the classroom (e.g.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Previous studies (Chukwuedo and Ementa, 2022; Okolie et al, 2021a; Okorie et al, 2022; Otache and Edokpolor, 2022) have found a positive and significant link between WPL and perceived employability, and employability preparatory behaviours. These findings are relevant given that, through WPL, higher education institutions (HEIs) can partner with industry to offer students opportunities to gain a practical understanding of work-related theoretical knowledge they may have gained in the classroom (e.g.…”
mentioning
confidence: 73%
“…Thus, we consider the ELT appropriate for learning the best instructional methods that WPL instructors may adopt to enhance students’ learning experience. This is important, given that no meaningful learning can take place during placements if the instructors are unable to use appropriate instructional methods to actively engage students in the experience, and motivate them to reflect on the learning experience, to develop personal conceptualizations of the ideas and to apply problem-solving skills in using the new ideas (Chukwuedo and Ementa, 2022; Okorie et al, 2022). Therefore, it is important to identify the best instructional methods that WPL instructors can adopt to provide students with opportunities to learn how to apply theoretical knowledge to real-world practice and transform their practical experiences into applied knowledge and skills that will foster their employability after graduation.…”
Section: Student Learning and Theoretical Underpinningmentioning
confidence: 99%
See 1 more Smart Citation
“…Work placement learning has numerous other benefits, including enhancing self-efficacy, work readiness, reflexive capabilities and networking (Chukwuedo and Ementa, 2022; Inceoglu et al, 2019; Otache and Edopkolor, 2022). However, students with disabilities often have a different experience with regards to work placements (Kim and Sellmaier, 2020; Langørgen and Magnus, 2018).…”
mentioning
confidence: 99%
“…This enables us to develop a new theoretical framework and perspective (Nguyen and Mogaji, 2022a; Snyder, 2019) for enhancing the work placement experience of students with disabilities in Nigeria. In doing so, we contribute to the existing body of work on innovative work placement practices (Chukwuedo and Ementa, 2022; Madichie and Agu, 2022; Otache and Edopkolor, 2022), on accommodating students with disabilities (Lindsay et al, 2021a; Moriña and Biagiotti, 2021), on students in business schools (Griffin and Coelhoso, 2019; Neelam et al, 2019), on support during work placement (Brooks and Youngson, 2016; Long and Fynn, 2018) and on universities’ and students' involvement in career preparatory behaviours as they engage with their work placement activities (Inceoglu et al, 2019; Okolie et al, 2020a).…”
mentioning
confidence: 99%